2001
DOI: 10.1128/aem.67.12.5849-5854.2001
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Microbial Communities in Soil, Rhizosphere, and Rhizoplane in Response to Crop Species, Soil Type, and Crop Development

Abstract: We investigated the influence of plant species, soil type, and plant development time on the shaping of microbial communities in soil and in association with roots. The sample group consisted of a total of 32 microcosms in three habitats: soil, rhizosphere, and rhizoplane. Communities were represented by the patterns of a sequence-specific separation of rRNA target sequences. Effects of experimental parameters were classified by a cluster analysis of pattern similarities. The type of plant species (clover, bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
174
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(189 citation statements)
references
References 31 publications
(18 reference statements)
10
174
1
2
Order By: Relevance
“…Factors responsible for changes in bacterial communities can include soil type, plant species and land management (Nü sslein and Tiedje, 1999;Wieland et al, 2001;Steenwerth et al, 2002;Buckley et al, 2006). Recent papers indicate that soil attributes are important in determining the structure and composition of bacterial communities, as well as affecting function (Hartman et al, 2008;Wakelin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Factors responsible for changes in bacterial communities can include soil type, plant species and land management (Nü sslein and Tiedje, 1999;Wieland et al, 2001;Steenwerth et al, 2002;Buckley et al, 2006). Recent papers indicate that soil attributes are important in determining the structure and composition of bacterial communities, as well as affecting function (Hartman et al, 2008;Wakelin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, soil bacterial and archaeal communities remained statistically indistinguishable among treatments after 5 years and through most of the 2-year sampling period that followed (Figure 2a). Research has shown that many characteristics of a plant assemblage-composition (Hunt et al, 1988;Bardgett et al, 1999;Smalla et al, 2001;Wieland et al, 2001;Nunan et al, 2003;Ayres et al, 2006), diversity (Gruter et al, 2006) and production (Zak et al, 2003)-can affect the microbial composition of underlying soils. Any snapshot measurement in our experiment might have affirmed this idea for our grassland system as well, but analyzing across seasons we find a soil community characterized by marked seasonal dynamics and longer-term decoupling from aboveground change.…”
Section: Resultsmentioning
confidence: 99%
“…These factors can alter not only the physical (Albuquerque et al, 1995) and chemical properties of the soil (Bayer and Mielniczuk, 1997) but also its microbial diversity and activity (Balota et al, 2004). The plant diversity of a production system exercises great influence on the structure of the microbial community of a soil, whether as a function of rhizospheric activity or of the amount and composition of organic C added to the system in the form of plant residues (Wieland et al, 2001). Because of these factors, cropping systems inevitably have impacts on soil processes, including fungistasis.…”
Section: Introductionmentioning
confidence: 99%